Penurunan Disleksia pada Balita Melalui Permainan Puzzle Alfabeth dan Kartu Huruf - Claudia, Juli Gladis; Sujawaty, Sri; Dunggio, Mutmainah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
Dyslexia is a disorder in the form of difficulty reading, writing, spelling which results in children not being able to read and speak. Teachers can stimulate children's thinking interested in learning to read using interesting learning techniques such as alphabet puzzle games and letter cards. This study aims to determine the effect of alphabet puzzle games and letter cards to reduce dyslexia. The research design is quasi-experimental with a one-group pretest-posttest design approach, namely measurement of observations before and after being given an alphabet puzzle game and letter cards for 3 months every 7 days. The research subjects were all students under five as many as 66 people. The dependent variable is alphabet puzzle and letter cards and the independent variable is the decrease in dyslexia. The results showed that there was a decrease in dyslexia in toddlers using alphabeth puzzle games (70% to 13%) and letter card games (67% to 16%). The results of the Paired T test statistical test obtained a Sig 2 tailed value of 0.000 (p < 0.05) meaning that there was an influence of alphabet puzzle games and letter cards on the decrease in dyslexia. The conclusion is that there is an effect of alphabet puzzle games and letter cards on the reduction of dyslexia in children under five.